2017
DOI: 10.1519/jsc.0000000000002219
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons in the Recovery Response From Resistance Exercise Between Young and Middle-Aged Men

Abstract: Gordon, JA III, Hoffman, JR, Arroyo, E, Varanoske, AN, Coker, NA, Gepner, Y, Wells, AJ, Stout, JR, and Fukuda, DH. Comparisons in the recovery response from resistance exercise between young and middle-aged men. J Strength Cond Res 31(12): 3454-3462, 2017-The purpose of this study was to compare the effects of a bout of high-volume isokinetic resistance exercise protocol (HVP) on lower-body strength and markers of inflammation and muscle damage during recovery between young and middle-aged adult men. Nineteen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 35 publications
4
30
2
Order By: Relevance
“…These results were consistent with the results of previous studies conducted in recreationally active [4,12] and resistance-trained individuals [13]. Previous studies in masters athletes, including endurance runners [30] and cyclists [31,32], have also reported that recovery of muscular voluntary contraction was not different between masters athletes and young athletes.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results were consistent with the results of previous studies conducted in recreationally active [4,12] and resistance-trained individuals [13]. Previous studies in masters athletes, including endurance runners [30] and cyclists [31,32], have also reported that recovery of muscular voluntary contraction was not different between masters athletes and young athletes.…”
Section: Discussionsupporting
confidence: 92%
“…In a small-scale study, recreationally-active middle-aged adults did not display a slower recovery from unaccustomed eccentric exercise of the elbow flexors than younger adults [12]. In addition, recreationally resistancetrained young and middle-aged adults also showed a similar pattern of recovery as assessed by markers of muscle damage following high-volume resistance exercise [13].…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Both groups consumed similar proportion of macronutrients (fat, carbohydrates, and protein) and energy intake. Peak torque comparisons between these groups have been previously reported (Gordon, et al, 2017). During isometric comparisons, YA was reported to have significantly greater average torque, rate Note.…”
Section: Resultsmentioning
confidence: 61%
“…Taken together with the significant correlation found at baseline, these findings may suggest that increases in muscle damage during HVP may by associated with decreased oxidation in the muscle observed during incremental exercise (Koga, Rossiter, Heinonen, Musch, & Poole, 2014;Spencer, Amano, Kondo, Kowalchuk, & Koga, 2014). Another factor that may have affected muscle oxidation differences between these age groups were differences in muscle strength and power (Gordon, et al, 2017). Although not measured, it is also possible that reduction in type 2 fiber size and changes in intrinsic contractile properties of muscle fibers with aging may have also contributed to the observed results (Callahan, et al, 2014).…”
Section: Discussionmentioning
confidence: 63%